Exports And Their Implications for The Position of Foreign Exchange Reserves in Indonesia 2005-2022 - Muhammad Ali; Ingrid Larasati Agustina; Tria Apriliana; Syafrizal Ikram; Suryana Suryana; Dudi Abdul Hadi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
The purpose of this study was to determine the effect of oil and gas exports and non-oil and gas exports on the position of foreign exchange reserves in Indonesia for the period 2005–2022. The discussion of this research relates to oil and gas exports, non-oil and gas exports, and the position of foreign exchange reserves. In this regard, the approach taken is theories related to the field. This research was conducted in Indonesia. This type of research is quantitative research. The data used in this study are secondary data of the time series type in the form of publications on oil and gas exports, non-oil and gas exports, and the position of foreign exchange reserves from 2005 to 2022 obtained from the Central Bureau of Statistics. The research method used in this study is the explanatory method. The data analysis technique in this study is descriptive analysis and multiple linear regression analysis. The results of this study partially show that there is no effect of oil and gas exports on the position of foreign exchange reserves, while non-oil and gas exports have an effect on the position of foreign exchange reserves. Simultaneously, it shows that there is an influence of oil and gas exports and non-oil and gas exports on the position of foreign exchange reserves.